2002
DOI: 10.3727/000000002783992352
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Promotes Amyloid Plaque Deposition in a Mouse Model of Alzheimer's Disease Neuropathology

Abstract: Several epidemiologic studies have reported that cyclooxygenase (COX) inhibitors prevent/delay the onset of Alzheimer's disease (AD). Recent experimental studies suggest that these compounds can also diminish amyloidβ (Aβ) neuropathology in rodent models of AD. To explore the relationship of COX expression to Aβ neuropathology, we crossed mice expressing both mutant amyloid precursor protein [K670N/M671L (APP swe )] and mutant PS1 (A246E) with mice expressing human COX-2 selectively in neurons. We show here th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 21 publications
6
93
0
Order By: Relevance
“…Our findings suggest a potential mechanism for the antiamyloid and proamyloid properties of NSAIDs and COX-2 overexpression, respectively, in transgenic models of mutant APP (Lim et al, 2001;Jantzen et al, 2002;Xiang et al, 2002;. The effects of EP2 receptor deletion may also be relevant to the preventive effects of chronic NSAID use against the development of AD (McGeer et al, 1996;Stewart et al, 1997;in t' Veld et al, 2001), in which decreased COX activity might lead to lower levels of downstream PGE 2 production and EP2 receptor signaling.…”
Section: Discussionmentioning
confidence: 90%
“…Our findings suggest a potential mechanism for the antiamyloid and proamyloid properties of NSAIDs and COX-2 overexpression, respectively, in transgenic models of mutant APP (Lim et al, 2001;Jantzen et al, 2002;Xiang et al, 2002;. The effects of EP2 receptor deletion may also be relevant to the preventive effects of chronic NSAID use against the development of AD (McGeer et al, 1996;Stewart et al, 1997;in t' Veld et al, 2001), in which decreased COX activity might lead to lower levels of downstream PGE 2 production and EP2 receptor signaling.…”
Section: Discussionmentioning
confidence: 90%
“…We cannot exclude the possibility that rofecoxib might accelerate conversion of MCI patients to AD, although this possibility would be at variance with the prior epidemiological and clinical data cited above, as well as the body of experimental evidence suggesting that COX-2 inhibition might attenuate neuronal death in several disease states including Parkinson's disease, multiple sclerosis, and amyotrophic lateral sclerosis, in addition to AD (Andreasson et al, 2001;Jain et al, 2002;Xiang et al, 2002;Giovannini et al, 2003;Scali et al, 2003;Teismann et al, 2003;Qin et al, 2003;Consilvio et al, 2004;Rose et al, 2004). The early onset of the treatment difference (and the lack of progressive widening of the difference over the course of the trial) further argues against a direct effect of rofecoxib on the underlying pathophysiology in AD.…”
Section: Discussionmentioning
confidence: 92%
“…Aβ42 accumulation may be a consequence of the increase in COX2 expression. Neuron-specific ectopic expression of human COX2 in the brain of a mouse model of Alzheimer's disease increased β-amyloid plaque formation and elevated Aβ40 and Aβ42 with no change in total APP, suggesting that COX2 influences APP processing (Xiang et al, 2002). Using an adenoviral gene transfer system to study the effects of COX1 and COX2 on β-amyloid generation, Qin and coworkers (2003) found that COXs promote Aβ generation via a PG-E2-mediated activation of γ -secretase, the membrane proteinase that generates Aβ40 and Aβ42.…”
Section: Discussionmentioning
confidence: 99%